TANGGAPAN BEBERAPA VARIETAS KUBIS (Brassica oleracea) TERHADAP FREKUENSI PEMBERIAN PUPUK MAJEMUK NPK - Khafsin Khafifi; Tyas Soemarah KURNIA DEWI; WIYONO WIYONO (JURNAL ILMIAH AGRINECA, 2011)
This research was conducted in the village of Wonosobo regency Kalikajar Wonosari District dated October 18, 2009 until January 18, 2010, aimed to know the response of some varieties of cabbage (brassica oleracea) with a factorial design with the basic pattern of Randomized Complete Block Design (Block), which consists of two factors, treatment ie (I) of cabbage varieties (V1 = Grand 11, V2 = Grand sharira, V3 = summer (II) The frequency of compound fertilizer NPK (F1 = One-time gift that is at the age of 7 days after planting, F2 = Two times a gift that is at the age of 7 days and 14 days after planting, F3 = Three times a gift that is at the age of 7 days,14 days and 21 days after planting. The results showed (1) treatment variety was very significant on weight of crop per plant, significant on weight of crop per plot, and non significant on height of plant, number of leaves, dry weight of crown, fresh weight of crown and diameter of crop. (2) the frequency of NPK compound fertilizer was very significant on weight of crop per plant and diameter crop, significant on height of plant, fresh weight of crown, dry weight of crown, weight of crop per plot and non significant onÂ  number of leaves. (3) a combination of variety and frequency of treatments NPK compound fertilizer had nonÂ  significant effect on all parameters, (4) The highest weight of crop and diameter crop. Significant on height of plantper plot obtained in the combined treatment V1F2 (11dan grand variety of fertilizer that is twice the age of 7 days and 14 days after planting ) that is equal to 12616.0 grams / plot (39,425 ton/ha) and lowest fresh weight of crop plots obtained in the combined treatment V3F3 (summer varieties and fertilizer is three times the age of 7 days, 14 days and 21 after planting) that is equal to 7613.2 grams / plot (23,79125 ton/ha).